2018
DOI: 10.1098/rsfs.2018.0006
|View full text |Cite
|
Sign up to set email alerts
|

The biomedical applications of graphene

Abstract: One contribution of 13 to a theme issue 'The biomedical applications of graphene'. This issue of Interface Focus is a collection of papers on 'The biomedical applications of graphene'. The idea to put together this theme issue evolved during discussions between Prof. Peter N.T. Wells CBE, FREng, FMedSci, FRS and myself in mid-2016. Very sadly, about a year ago, Prof. Wells passed away. However, before that and even in the various last stages of his life he was intensely involved in planning this theme issue wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Graphene is found in a wide variety of forms which are 0D (in the form of graphene quantum dots (GQDs)), 1D (in the form of nanowires, and tubes), 2D (in the form of pristine graphene, fluorographene, graphene oxide (GO), reduced graphene oxide (rGO), porous graphene (PG), graphene nanoplatelets (GNPs), graphene nanoribbons), 3D (in the form of graphene foam, graphene aerogels). Graphene and its derivatives have extensively been explored for extended applications including [24] drug delivery, [25,26] tissue engineering, [26] sensor technologies, [27] coatings for corrosion protection, [28] and antimicrobial agents. [4,12,14,15,29] (Figure 1a,b) The fact that graphene and GO nanomaterials have a high surface area as a nanotherapeutic drug delivery platform and the high drug loading capacity of a single layer makes them attractive in this field.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene is found in a wide variety of forms which are 0D (in the form of graphene quantum dots (GQDs)), 1D (in the form of nanowires, and tubes), 2D (in the form of pristine graphene, fluorographene, graphene oxide (GO), reduced graphene oxide (rGO), porous graphene (PG), graphene nanoplatelets (GNPs), graphene nanoribbons), 3D (in the form of graphene foam, graphene aerogels). Graphene and its derivatives have extensively been explored for extended applications including [24] drug delivery, [25,26] tissue engineering, [26] sensor technologies, [27] coatings for corrosion protection, [28] and antimicrobial agents. [4,12,14,15,29] (Figure 1a,b) The fact that graphene and GO nanomaterials have a high surface area as a nanotherapeutic drug delivery platform and the high drug loading capacity of a single layer makes them attractive in this field.…”
Section: Introductionmentioning
confidence: 99%
“… 40 Furthermore, the high dispersibility and hydrophilicity of GO improve tensile strength by creating hydrogen bonds between the filler and matrix in composite materials, which is a significant attribute for wound dressing materials. 41 43 …”
Section: Introductionmentioning
confidence: 99%
“…Membranes using graphene oxide (GO) have a high-water vapor transfer rate, as well as excellent water and exudate absorption, mechanical strength, and cytocompatibility . Furthermore, the high dispersibility and hydrophilicity of GO improve tensile strength by creating hydrogen bonds between the filler and matrix in composite materials, which is a significant attribute for wound dressing materials. …”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been reported on graphene and its derivatives and their nanocomposites discussing antibacterial, antifungal and antiviral activities (18)(19)(20)(40)(41)(42). Matharu et al investigated the antibacterial activity of 2, 4 and 8 w/w% concentration graphene nanoplatelet (GNP) and GO loaded polymethylmethacrylate (PMMA) composite nanofibers against Escherichia coli (E. coli) (19,20).…”
Section: Introductionmentioning
confidence: 99%